A stepwise multi-assignment spreadsheet model to select student teams - Celik, Bilge Gokhan; Brunnhoeffer, Gilbert C. F. (International Journal of Engineering and Technology, 2013)
Student projects play a big role in engineering and management education. Most projects require students to work in teams, which allow students to practice their technical knowledge, foster the development of personal leadership skills, and teach the value of team accomplishments. One of the challenges of administering team projects is to create the best team compositions that give all teams the equal chance of success while maximizing interaction between students. The instructor should strive to balance each team so the team capabilities are as even as possible. Instructors also should take into account the performance of each student throughout the semester, when recreating teams for upcoming assignments. This paper presents a stepwise optimization that continues throughout the semester as the teams evolve from one assignment to another. Results show that this method can expose students to approximately 50% of their classmates within four team assignments and reasonable team grade variance.